How Do They Find Their Place? A Longitudinal Study of Management Students' Attitudes and Motivations During Their First Year at Business School - Jenert, Tobias; Brahm, Taiga
The first year of studying has been extensively researched applying different theoretical lenses to better understand the transition into Higher Education (HE). It is of particular interest to investigate how students deal with frictions between themselves as individuals and what they perceive to be dominant features of the first-year culture of their studies. To tackle this question, a qualitative longitudinal study was conducted. Based on a sociocultural understanding of attitudes and motivations, its aim was to closely follow a relatively small but highly diverse sample of students throughout their first year at a business school in order to develop an in-depth understanding of each individual’s motivational and attitudinal development.
Keywords: Enculturation; first-year students; beginning students; retention; drop-out

The crucial first year: Students’ motivation at a Swiss Business School--a longitudinal study - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Academy of Management Proceedings)
Despite students’ motivation being considered a strong predictor of performance, the development of motivation of business school students has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. This is surprising, as the transition from school to university is a crucial phase in the academic career and can be overwhelming for some students. The present study addresses this research gap and examines the development of economics and management students’ study motivation. The longitudinal study included four waves of data collected throughout the first year using quantitative surveys. Regarding students’ development over time, the analysis showed a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline

Zwischen Individuum, Institution und Disziplin: Methodologische Überlegungen zur Erfassung von Lernkulturen an Hochschule - Jenert, Tobias; Reinmann, Gabi (Dokumentation der Jahrestagung der Sektion Erwachsenenbildung der DGfE)
Keywords: Methodologie; Lernforschung; hochschuldidaktische Forschung; Higher Education

Zwischen" netten" Tools und" Überdidaktisierung": Neue Medien in der Hochschuldidaktik - Wagner, Dietrich; Jenert, Tobias
Auswertung einer Befragung unter Studierenden zu der Frage welche Elemente eine Lehrveranstaltung innovativ machen und welche Rolle die neuen Medien dabei spielen. Digitale Medien begegnen uns in der Hochschule immer wieder. Häufig handelt es sich um neue Werkzeuge oder Trends (Klicker, MOOCs, Web 2.0), die einerseits potenzialreich und spannend erscheinen, deren didaktische Verwertbarkeit sich aber nicht auf den ersten Blick erschließt. Oft folgt nach einer euphorischen Erprobung schnell die Ernüchterung, wenn festgestellt wird, dass sich durch die digitalen Technologien allein kein erhöhter Lernerfolg ergibt und auch die Studierenden keine nachhaltigen Motivationsschübe erfahren. Aus der Hochschuldidaktik hört man häufig und berechtigterweise kritische Stimmen, welche die Einbettung digitaler Medien in sorgfältig geplante didaktische Arrangements betonen. Es stellt sich die Frage, inwieweit damit die Kreativität und der Entdeckergeist von Lehrenden und Studierenden eingeschränkt werden. Wir wollen im Disq-Space der Frage nachgehen, wie die Hochschuldidaktik auf neue digitale Trends reagieren und dabei einen Mittelweg zwischen "kreativem Ausprobieren" und pädagogisch-didaktischer Rationalität einschlagen kann. Zunächst werden die Ergebnisse einer aktuellen Umfrage an der Universität St. Gallen zu den Vorstellungen Studierender zu innovativer Lehre vorgestellt. Nach einer Öffnung des Raums für gute sowie schlechte Erfahrungen und Bespiele von Seiten der Teilnehmenden soll diskutiert werden, welche personellen, didaktischen und organisatorischen Voraussetzungen erfüllt sein müssen, damit Digitalisierung die Kompetenzentwicklung der Studierenden unterstützt. Die Ergebnisse der Diskussionsrunde werden im Blog des Teams Hochschulentwicklung zur Verfügung gestellt. Es wird angestrebt, diese damit einer breiteren Öffentlichkeit zugänglich zu machen.
Keywords: Neue Medien; Hochschuldidaktik; Studierende; Innovation in der Lehre

On the iterative plug-in algorithm for estimating diurnal patterns of financial trade durations - Feng, Yuanhua; Forstinger, Sarah; Peitz, Christian (Journal of Statistical Computation and Simulation)

Forecasting financial market activity using a semiparametric fractionally integrated Log-ACD - Feng, Yuanhua; Zhou, Chen (International Journal of Forecasting)

Empirical Economic and Financial Research - Theory, Methods and Practice

Introduction - Beran, Jan; Feng, Yuanhua; Hebbel, Hartmut (Empirical Economic and Financial Research)

An iterative plug-in algorithm for realized kernels - Feng, Yuanhua; Zhou, Chen

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.